Comparative whey proteome analysis of small-tailed Han and DairyMeade ovine milk. Issue 4 (6th November 2021) - Bai, Urhan; Su, Xiaohu; Zheng, Zhong; Zhang, Liguo; Ma, Ying; Dou, Yingjie; Zhang, Xiaoran; Su, Guanghua; Zhou, Ningcong; Li, Guangpeng; Zhang, Li
Abstract: We characterized the proteome profile of mid-lactation small-tailed Han (STH) and DairyMeade (DM) ovine milk in order to explore physiological variation and differences in milk traits between the two breeds. Methodology combined a tandem mass tag (TMT) proteomic approach with LC-MS/MS technology. A total of 656 proteins were identified in STH and DM ovine milk, of which 17and 29 proteins were significantly upregulated ( P < 0.05) in STH and DM, respectively. Immune-related proteins and disease-related proteins were highly expressed in STH milk, whereas S100A2 and AEBP1 were highly expressed in DM milk, which had beneficial effects on mammary gland development and milk yield. Our results provide a theoretical basis for future breeding of dairy sheep.